Effect of mental rotation skills training on ultrasound-guided regional anaesthesia task performance by novice operators: a rater-blinded, randomised, controlled study. (August 2020) - Hewson, David W.; Knudsen, Rasmus; Shanmuganathan, Sanjeevan; Ferguson, Eamonn; Hardman, Jonathan G.; Bedforth, Nigel M.; McCahon, Rob A.
Abstract: Background: The effect of mental rotation training on ultrasound-guided regional anaesthesia (UGRA) skill acquisition is currently unknown. In this study we aimed to examine whether mental rotation skill training can improve UGRA task performance by novice operators. Methods: We enrolled 94 volunteers with no prior experience of UGRA in this randomised controlled study. After a baseline mental rotation test, their performance in a standardised UGRA needling task was independently assessed by two raters using the composite error score (CES) and global rating scale (GRS). Volunteers with low baseline mental rotation ability were randomised to a mental rotation training group or a no training group, and the UGRA needling task was repeated to determine the impact of the training intervention on task performance. The study primary outcome measure was UGRA needling task CES measured before and after the training intervention. Results: Multivariate analyses controlling for age, gender, and previous performance showed that participants exposed to the training intervention made significantly fewer errors (CES B =-0.66 [standard error, se =0.17]; P <0.001; 95% confidence interval [CI], -0.92 to -0.26) and displayed improved overall performance (GRS B =6.15 [se =2.99], P =0.048, 95% CI=0.06 to 12.13) when undertaking the UGRA needling task. Conclusions: A simple training intervention, based on the manipulation and rotation of three-dimensional models, results in improved technical performance of a UGRA needling task in operators with low baseline mental rotation skills.